Ethnonyms in Latvian Texts of the 16–17th Centuries: Latvians, Lithuanians, Russians - Trumpa, Anta (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]This article discusses the usage of ethnonyms denoting Latvians, Lithuanians and Russians in 16–17th century Latvian texts that are included in the Corpus of Early Latvian Texts. The objective of this article is to analyze the details of how these ethnonyms are used in these texts, the meanings attributed to them (especially in the case of ethnonyms denoting Lithuanians and Russians) and the differences from their usage in folklore.It is concluded that latvietis and latvis – two ethnonyms denoting Latvians – can be found in texts (including unpublished manuscripts) dating back as early as the 17th century. The majority of them are practical texts, such as dictionaries, but there are original religious texts addressed to Latvians themselves, too – e.g., Eernst Glück’s preface to his New Testament translation of 1685, or the sermon books by Georg Mancelius.The ethnonyms denoting Lithuanians – such as leitis, lietaviets and lietavnieks – also appear in 17th century dictionaries, occasionally also in the sermons by Mancelius. However, it is not always possible to tell whether these terms are used to denote an ethnicity or the inhabitants of the respective country. Unlike Latvian folksongs, the 17th century texts never use the ethnonym leiši to refer to Latvians.Regarding the ethnonym denoting Russians in the early Latvian texts, there are several differences from the usage of denotations of Latvians and Lithuanians: 1) The word krievs (“Russian”) appears already in the 16th century; 2) It is included not only in the first Latvian lexicographical sources and in original religious texts (for instance the sermon books), but also in translated religious texts, where it has been employed as an equivalent of the ethnonyms used in the original texts; 3) In the 17th century, the word krievs has sometimes been included in compound botanic terms denoting plants introduced from other countries.